Selective Disclosure: Exploring Web-Based Accountability Strategies of Charitable NPOs in Indonesia - Suandi, Aprilia Beta; Asrimiyanti, Rahmi (Jurnal REKSA: Rekayasa Keuangan, Syariah dan Audit, 2025)
Technological advancements have transformed how organizations deliver accountability. This study investigates how Indonesian charitable Non-Profit Organizations (NPOs) utilize their websites for accountability. Analyzing 33 zakat institutions, the study focuses on five dimensions: accessibility, engagement, financial disclosure, operational disclosure, and governance, using 35 indicators. Applying Social Exchange Theory, the study reveals varied accountability levels, with higher levels in online-specific dimensions and selective sharing in traditional areas, especially financial disclosure, which may be influenced by concerns over misinterpretation and criticism. This implies that NPOs might prioritize information perceived as beneficial for reciprocal relationships, potentially leading to reluctance in full financial transparency. Despite government mandates to submit financial reports, many NPOs chose not to display this information on their websites, indicating a possible selective accountability approach. This study fills a gap in the literature on web-based accountability for charitable NPOs in emerging countries, particularly religious-based institutions, offering insights into their accountability practices and enriching the non-profit sector discourse.